Resposta :
Resposta:
(-4)^9:(-4)^3.(-4)^a=(-4)^10
(-4)^9÷(-4)^3×(-4)^a=(-4)^10
Dada que a função exponencial com base negativa é identificada, a equação não tem solução
![Ver imagem SIMONESANTOSARAUJO91](https://pt-static.z-dn.net/files/d8c/f94870936ae8dc8ff734a9259edc459c.jpg)
![Ver imagem SIMONESANTOSARAUJO91](https://pt-static.z-dn.net/files/dce/82ac0f9ee11f8e0706df42edd37f805b.jpg)
Resposta:
(-4)^9:(-4)^3.(-4)^a=(-4)^10
(-4)^9÷(-4)^3×(-4)^a=(-4)^10
Dada que a função exponencial com base negativa é identificada, a equação não tem solução